2011
DOI: 10.4103/0972-5229.92074
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter-related bloodstream infections in the intensive care unit

Abstract: Context:Central venous catheter-related bloodstream infection (CRBSI) is associated with high rates of morbidity and mortality in critically ill patients.Aims:This study was conducted to determine the incidence of central venous catheter-related infections (CRIs) and to identify the factors influencing it. So far, there are very few studies that have been conducted on CRBSI in the intensive care unit in India.Settings and Design:This was a prospective, observational study carried out in the medical intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 44 publications
7
57
5
1
Order By: Relevance
“…Other studies conducted by H. V Patil, [19] Deepti et al, [15] showed high CRBSI rate among 50-60 years of age group whereas study done by Manjula et al [21] showed high culture positivity rate between 19-30 years of age group.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Other studies conducted by H. V Patil, [19] Deepti et al, [15] showed high CRBSI rate among 50-60 years of age group whereas study done by Manjula et al [21] showed high culture positivity rate between 19-30 years of age group.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies also showed male predominance like the study done by H.V Patil [19] which showed 59% males and 41% females were affected, the study done by Deepti et al [15] showed 69% males and 31% females affected, the study done by Daniela Bicudo [17] showed 58.85 males and 41.2% females affected and the study by Ramanathan Parameswaran et al [16] showed 72% males and 28% females were affected. CRBSI rates were high in all these studies because of associated or predisposing factors which were seen more in males like smoking, alcohol intake and comorbid illness like HTN, DM, ketoacidosis bronchial asthma, COPD, renal failure, patient on immune suppressive therapy, chemotherapy, etc.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results are not consistent with the findings of other observers. 8,[20][21][22][23] All the isolates of K. pueumoniae were resistant to ampicillin and amoxicillin/clavulanic acid. Amikacin was resistant to (58.33%) isolates and was lowest among all commonly used antibiotics.…”
Section: Observationsmentioning
confidence: 99%
“…2 Data regarding the incidence, prevalence, epidemiology, aetiology and susceptibility pattern of isolates are frequently available from the resource rich countries but same is not true for resource poor countries. [3][4][5][6][7][8] Both gram positive and gram negative organisms are responsible for CLABSI. Gram positive cocci (both Staphylococcus aureus and the coagulasenegative staphylococci) are the leading causes of CLABSI followed by Gram negative bacilli.…”
Section: Introductionmentioning
confidence: 99%